Loanwords for language learners: Help or hindrance? - Kaori Nakao (Vocabulary Learning and Instruction, 2016)
Background: Loanwords are a growing component of the Japanese language. During the past six decades, the majority of new loanwords entering the Japanese language have come from the English language. For native Japanese speaking students, loanwords are a source of potential frustration and support, both within their L1 and L2 (English). Aims: To explore and further our understanding of students’ knowledgeof high frequency loanwords. Sample: One hundred thirty undergraduate students of mixed major, studying in a compulsory course (Eigo/Eigokaiwa), at Kyushu Sangyo University, participated in this exploratory study.Methods: This study compares loanword self-reported difficulty (L2) with students’ productive knowledge in their L1. This study was undertaken with a group of first- and second-year students (n!130) enrolled incompulsory English classes.Results: For half of the loanwords examined, self-reported difficulty and students’ productive knowledge was consistent. The remaining words examined were inconsistent with self-report measures, generally underestimating students’ actual productive knowledge. Conclusions: Error analyses of students’ L1 sentences indicated that inconsistencies observed between self-report and productive knowledge may be due to students’ partial knowledge of words expressed through their reliance on katakana translations of the words tested. Implications for practice and future directions are discussed.